2019
DOI: 10.4274/tjps.95967
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Galantamine in <i>Sternbergia</i> Species by High Performance Liquid Chromatography

Abstract: ÖZAmaç: Bu çalışmada Türkiye'de yetişen Sternbergia türlerinin galantamin içeriklerinin kalitatif ve kantitatif analizi amaçlanmıştır. Gereç ve Yöntemler:Galantamin Sternbergia fischeriana yumrularından izole edilmiş ve yapısı spektroskopik yöntemler kullanılarak aydınlatılmıştır.Sternbergia lutea subsp. lutea, S. lutea subsp. sicula, Sternbergia candida, S. fischeriana ve Sternbergia clusiana türlerinin galantamin içeriği kalitatif ve kantitatif olarak yeni geliştirilen ve valide edilmiş bir yüksek performans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…In a study conducted by Tanker et al, S. clusiana was found to exhibit analgesic activity due to the presence of the major alkaloids, lycorine and hemanthamine [ 17 ]. Other studies have reported that S. clusiana species are important sources of the anticholinesterase agent galantamine, currently known for being highly effective in treating Alzheimer disease [ 18 , 19 ]. Besides its antifungal properties [ 20 ], S. clusiana was also suspected to have anticancerous potential due to its richness in Amaryllidaceae alkaloids (AA) such as lycorine [ 17 , 21 ], which was previously shown to be effective in the regulation of malignant cell invasion and metastasis [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted by Tanker et al, S. clusiana was found to exhibit analgesic activity due to the presence of the major alkaloids, lycorine and hemanthamine [ 17 ]. Other studies have reported that S. clusiana species are important sources of the anticholinesterase agent galantamine, currently known for being highly effective in treating Alzheimer disease [ 18 , 19 ]. Besides its antifungal properties [ 20 ], S. clusiana was also suspected to have anticancerous potential due to its richness in Amaryllidaceae alkaloids (AA) such as lycorine [ 17 , 21 ], which was previously shown to be effective in the regulation of malignant cell invasion and metastasis [ 22 ].…”
Section: Introductionmentioning
confidence: 99%